PENGARUH ZAT ADDITIVE TIPE F UNTUK BET-ON FAST TRACK OPEN TRAFFIC DALAM 7 HARI - Pradesta, Eka Raza; Hendardi, Agi Rivi; Nurdianto, Risnandar (Universitas Perjuangan Tasikmalaya, 2024)
Abstract— Concrete is a construction material that is widely used in modern building structures. Basically, concrete has basic properties, namely strong against compressive stress and weak against tensile stress. The compressive strength of concrete is influenced by the type of ingredients that make it up, including admixtures. In some cases, concrete mixtures require additional ingredients to support their performance, with chemical or physical additives in certain proportions. The purpose of this additive is to change one or more of the properties of the concrete, when it is fresh or after it has hardened. This research aims to determine the effect of adding type F additives to 7 day open traffic fast track concrete. Research has been carried out on 4 variations of concrete mixtures with additives with a design compressive strength of 30 MPa. The concrete mixture used is type F additive which was tested at 7 days, 14 days and 28 days with variations of 0%, 0.2%, 0.4%, 0.6% with 9 samples for each variation. The results of research taken from concrete aged 7 days as a reference show that the average compressive strength of normal concrete is 20.38 MPa, and exceeds the design compressive strength at 28 days of 31.52 MPa, and with a mixture variation of 0.2% at 7 days. days obtained an average compressive strength of 21.70 MPa and exceeded the design compressive strength of 32.27 MPa at the age of 28 days with a better increase over normal concrete, for concrete with a mixture of 0.4% the average strength obtained at the age of 7 days was 20.19 MPa, experienced a decrease from normal concrete but reached the planned compressive strength at 28 days of 30.76 MPa, and for the 0.6% mix variation the average compressive strength at 7 days was 18.59. MPa, decreased coMPared to normal concrete and did not reach the design compressive strength at 28 days, an average of 25.29 MPa. Using too many additives has a decreasing iMPact on the strength of the concrete. It is recommended to pay attention to several factors such as mix design calculations, slump, and calibration for the tools and materials used. Keywords — Concrete, Compressive Strength, Slump, Additive Type F Abstrak— Beton merupakan salah satu bahan konstruksi yang banyak dipergunakan dalam struktur bangunan modern. Pada dasarnya beton memiliki sifat dasar, yaitu kuat terhadap tegangan tekan dan lemah tehadap tegangan tarik. Kuat tekan beton dipengaruhi oleh jenis bahan penyusunnya termasuk bahan tambah (admixture). Dalam beberapa kasus, campuran beton memerlukan bahan tambah untuk menunjang performanya, dengan bahan tambahan (aditif) yang bersifat kimiawi ataupun fisikal pada perbandingan tertentu. Tujuan bahan tambah ini yaitu mengubah satu atau lebih dari sifat beton, sewaktu dalam keadaan segar atau setelah mengeras. Penelitian ini bertujuan untuk mengetahui pengaruh penambahan zat aditif tipe F pada beton fast track open traffic 7 hari. Penelitian telah dilakukan pada 4 variasi campuran beton dengan zat aditif dengan kuat tekan rencana 30 MPa. Adapun campuran beton yang digunakan adalah zat aditif tipe F yang diuji pada umur 7 hari, 14 hari, dan 28 hari dengan variasi 0%, 0,2 %, 0,4%, 0,6% dengan masing-masing variasi berjumlah 9 sampel. Hasil penelitian yang diambil dari umur beton 7 hari sebagai acuan menunjukkan kuat tekan rata-rata beton normal sebesar 20,38 MPa, dan melebihi kuat tekan rencana pada umur 28 hari sebesar 31,52 MPa, dan pada variasi campuran 0,2% diumur 7 hari didapat kuat tekan rata-rata sebesar 21,70 MPa dan melebihi kuat tekan rencana sebesar 32,27 MPa diumur 28 hari dengan peningkatan yang lebih baik melebihi beton normal, untuk beton dengan campuran 0,4% didapat kuat rekan rata-rata pada umur 7 hari sebesar 20,19 MPa, mengalami penurunan dari beton normal akan tetapi mencapai kuat tekan rencana diumur 28 hari sebesar 30,76 MPa, dan untuk variasi campuran 0,6% didapat kuat tekan rata-rata pada umur 7 hari sebesar 18,59 MPa, mengalami penurunan dibandingkan beton normal dan tidak mencapai kuat tekan rencana pada umur 28 hari rata-rata sebesar 25,29 MPa. Penggunaan zat aditif terlalu banyak memberikan daMPak penurunan pada kekuatan beton. Disarankan agar memperhatikan beberapa faktor seperti perhitungan mix design, slump, dan kalibrasi untuk alat dan bahan yang digunakan. Kata kunci — Beton, Kuat Tekan, Slump, Zat Aditif Tipe F